Antifungal essential oils in dental practice - Carvalho, Driany Tamami Yamashita de; Souza, Heide Mendonça Moreira de; Assis , Priscila Helena; Ortolani , Cristina Lúcia Feijó (Seven Editora, 2024)
Introduction: The World Health Organization (WHO) has recently included fungi in the list of priority pathogens. The pathogenic yeast C. albicans is responsible for candidiasis in the mouth, throat and esophagus due to its high antifungal resistance and responsible for the number of deaths. In recent years there has been a considerable increase in interest in the practice of phytotherapy, mainly due to the emergence of new fungal strains resistant to antifungals. Herbal compounds have been used in medicine and dentistry for centuries. A classic example is the use of clove oil to treat tooth decay, and eugenol, its main active ingredient, is still used today in daily dental practice. They have been widely studied for their therapeutic grade, for biological and pharmacological tests and for their chemical constituents. Objective: In this integrative review study, the effects of essential oils, their potential benefits for use and their constituents on fungal micromorphology will be evaluated regarding their biological properties in the context of oral health care, helping to expand the knowledge of their mechanisms of action, in addition to provide an overview of the current literature. Methodology: Two indexed search databases Lilac and Pubmed were consulted in March 2024. The words "DENTISTRY" AND "VOLATILE OILS" and "antifungal" and Boolean AND were used, and 11 articles were found that were analyzed. Inclusion criteria: be in agreement with the proposed theme, in the free articles version. Exclusion criteria: not agreeing with the proposed theme. Results: The resident microbiota of the mouth is quite diverse, eight species of the genus Candida were considered pathogenic, and Candida tropicalis and Candida krusei, are associated with the pathological process, especially to promote the formation of biofilms and increase drug resistance. The herbal medicines used for the treatment of oral diseases in the studies showed antifungal activity and can also be used as an antiseptic. Conclusion: According to the literature reviewed, many plants and their chemical compounds have antifungal action. Scientific studies prove the effectiveness of essential oils, considered an herbal medicine and its advantages in relation to allopathic medicines used in Dentistry and are considered promising agents for the development of new bioproducts applicable in the clinical routine. DOI:https://doi.org/10.56238/sevened2024.007-050